2015
DOI: 10.5853/jos.2015.17.1.38
|View full text |Cite|
|
Sign up to set email alerts
|

Case Characteristics, Hyperacute Treatment, and Outcome Information from the Clinical Research Center for Stroke-Fifth Division Registry in South Korea

Abstract: Characteristics of stroke cases, acute stroke care, and outcomes after stroke differ according to geographical and cultural background. To provide epidemiological and clinical data on stroke care in South Korea, we analyzed a prospective multicenter clinical stroke registry, the Clinical Research Center for Stroke-Fifth Division (CRCS-5). Patients were 58% male with a mean age of 67.2±12.9 years and median National Institutes of Health Stroke Scale score of 3 [1-8] points. Over the 6 years of operation, tempor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
183
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

8
2

Authors

Journals

citations
Cited by 196 publications
(196 citation statements)
references
References 47 publications
(35 reference statements)
4
183
1
Order By: Relevance
“…Detailed information from the Clinical Research Center for Stroke-5th division registry was reported previously. 11,12 Fourteen stroke centers with nationwide coverage registered 28 348 acute stroke patients consecutively between April 2008 and November 2013. For the current study, 17 976 patients registered between January 2011 and November 2013 were initially screened.…”
Section: Subjectsmentioning
confidence: 99%
“…Detailed information from the Clinical Research Center for Stroke-5th division registry was reported previously. 11,12 Fourteen stroke centers with nationwide coverage registered 28 348 acute stroke patients consecutively between April 2008 and November 2013. For the current study, 17 976 patients registered between January 2011 and November 2013 were initially screened.…”
Section: Subjectsmentioning
confidence: 99%
“…11 The registry includes consecutive acute stroke or transient ischemic attack cases from 12 academic and regional stroke centers across the nation (Figure 1). The collection of clinical information for the Clinical Research Center for Stroke 5th division registry was approved by the local institutional review boards in all participating centers with a waiver of patient consent because of the anonymity of the collected data and the minimal risk to participants.…”
Section: Patients and Work-upmentioning
confidence: 99%
“…12,13 The collaborative registry study group consisted of 14 academic and regional tertiary stroke centers. Detailed information on the CRCS-5 registry is given in the online-only Data Supplement.…”
Section: Subjectsmentioning
confidence: 99%